2019
DOI: 10.1016/j.seizure.2019.05.017
|View full text |Cite
|
Sign up to set email alerts
|

PRRT2 mutations in Japanese patients with benign infantile epilepsy and paroxysmal kinesigenic dyskinesia

Abstract: This study was performed to clarify the clinical features of Japanese patients with PRRT2 mutations. Methods: The PRRT2 gene was analyzed in 135 patients with benign infantile epilepsy (BIE) or paroxysmal kinesigenic dyskinesia (PKD) using a direct sequencing method: 92 patients had BIE alone, 25 had both BIE and PKD, and 18 had PKD alone. Of the cases, 105 were familial, and 30 were sporadic. Clinical information was collected using a structured questionnaire. Results: PRRT2 mutations were identified in 104 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
(52 reference statements)
5
11
0
Order By: Relevance
“…Outcome of patients with PRRT2 -associated disorders is usually favorable. In the present study, the average age of remission of patients with BFIE was 8.5 ± 5.0 months, which was similar to previously published data ( 29 ). Most patients had normal psychomotor development at last follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Outcome of patients with PRRT2 -associated disorders is usually favorable. In the present study, the average age of remission of patients with BFIE was 8.5 ± 5.0 months, which was similar to previously published data ( 29 ). Most patients had normal psychomotor development at last follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…The double occurrence of PRRT2 mutations in a patient with PKD has been previously reported with intelligent disability [20]. While several studies reported that homozygous mutations cause sever neurological symptoms, recent reported c.981C>G homozygous mutation has not resulted in severe disorder [33]. Consistent with our result, this supports the hypothesis that differences in the epilepsy phenotypes in the patients with PRRT2 mutations depend on the types of PRRT2 mutations.…”
supporting
confidence: 92%
“…Decreased nodal centrality in the MTG has also been reported in epilepsy (M. Liu, Chen, Beaulieu, & Gross, 2014), which may partly explain both the overlap of symptoms between PKD and epilepsy and the therapeutic effect of antiepileptic agents in PKD. It is also noteworthy that PRRT2 mutations were identified in both PKD patients and epilepsy patients (Okumura et al, 2019). We suggest that the nodal alterations in the temporal lobe observed only in PKD‐M patients may be induced by PRRT2 mutations.…”
Section: Discussionmentioning
confidence: 99%